Kajian Tanaman Obat Indonesia yang Berpotensi sebagai Antidepresan - Adelina, Rosa (Jurnal Kefarmasian Indonesia, 2013)
Depression as a mental illness has many negative effects to people’s quality of life. The synthetic drugs has been developed to cure this illness but the side effect has compromized the therapy. Other side, the use of herbal medicine has been accepted in almost country in the world.The objective of this study is to find antidepressant drug from Indonesian herbal medicine. The study is an assessment derived from 53 publications of antidepressant effect of Indonesian herbal from national and international papers.The assessment include the active compounds, mechanism, and used part of plant. The result of this study is there are nine potential Indonesian plants to be a co-therapy or alternative drug as antidepressant. They are Valeriana javanica, Areca catechu Linn, Piper longumBl., Curcuma longaLinn, Momordica charantia Linn, Clitoria ternatea, Morinda citrifolia, Myristica fragrans, and Ocimum basilicum